Analysis of a small outbreak of Shiga toxin-producing Escherichia coli O157:H7 using long-read sequencing. Issue 3 (8th March 2021) - Greig, David R.; Jenkins, Claire; Gharbia, Saheer E.; Dallman, Timothy J.
Abstract : Compared to short-read sequencing data, long-read sequencing facilitates single contiguous de novo assemblies and characterization of the prophage region of the genome. Here, we describe our methodological approach to using Oxford Nanopore Technology (ONT) sequencing data to quantify genetic relatedness and to look for microevolutionary events in the core and accessory genomes to assess the within-outbreak variation of four genetically and epidemiologically linked isolates. Analysis of both Illumina and ONT sequencing data detected one SNP between the four sequences of the outbreak isolates. The variant calling procedure highlighted the importance of masking homologous sequences in the reference genome regardless of the sequencing technology used. Variant calling also highlighted the systemic errors in ONT base-calling and ambiguous mapping of Illumina reads that results in variations in the genetic distance when comparing one technology to the other. The prophage component of the outbreak strain was analysed, and nine of the 16 prophages showed some similarity to the prophage in the Sakai reference genome, including the stx2a -encoding phage. Prophage comparison between the outbreak isolates identified minor genome rearrangements in one of the isolates, including an inversion and a deletion event. The ability to characterize the accessory genome in this way is the first step to understanding the significance of these microevolutionary events and their impact on the evolutionary history, virulence and potentially the likely source and transmission of this zoonotic, foodborne pathogen.